Resurgence as Choice in Context: Treatment duration and on/off alternative reinforcement. Issue 1 (27th November 2019) - Shahan, Timothy A.; Browning, Kaitlyn O.; Nall, Rusty W.
Abstract : Resurgence as Choice (RaC) is a quantitative theory suggesting that an increase in an extinguished target behavior with subsequent extinction of an alternative behavior (i.e., resurgence) is governed by the same processes as choice more generally. We present data from an experiment with rats examining a range of treatment durations with alternative reinforcement plus extinction and demonstrate that increases in treatment duration produce small but reliable decreases in resurgence. Although RaC predicted the relation between target responding and treatment duration, the model failed in other respects. First, contrary to predictions, the present experiment also replicated previous findings that exposure to cycling on/off alternative reinforcement reduces resurgence. Second, RaC did a poor job simultaneously accounting for target and alternative behaviors across conditions. We present a revised model incorporating a role for more local signaling effects of reinforcer deliveries or their absence on response allocation. Such signaling effects are suggested to impact response allocation above and beyond the values of the target and alternative behaviors as longer‐term repositories of experience. The new model provides an excellent account of the data and can be viewed as an integration of RaC and a quantitative approximation of some aspects of Context Theory.